MASCC/ISOO expert opinion on the management of oral problems in patients with advanced cancer - Davies, Andrew (My University, 2022)
Purpose: The Palliative Care Study Group in conjunction with the Oral Care Study Group of the Multinational Association for Supportive Care in Cancer (MASCC) formed a sub-group to develop evidence-based guidance on the management of common oral problems in patients with advanced cancer. Methods: This guidance was developed in accordance with the MASCC Guidelines Policy. A search strategy for Medline was developed, and the Cochrane Database of Systematic Reviews and the Cochrane Central Register of Controlled Trials were explored for relevant reviews and trials, respectively. Guidance was categorised by the level of evidence, and "category of guideline" (i.e., "recommendation", "suggestion" or "no guideline possible"). Results: Twelve generic suggestions (level of evidence - 5), three problem-specific recommendations and 14 problem-specific suggestions were generated. The generic suggestions relate to oral hygiene measures, assessment of problems, principles of management, re-assessment of problems and the role of dental/oral medicine professionals. Conclusions: This guidance provides a framework for the management of common oral problems in patients with advanced cancer, although every patient requires individualised management.
PUBLISHED
Keywords: Neoplasms; Oral hygiene; Oral manifestations; Oral problems; Palliative care; Practice guideline; Cancer